DVD studio pro 2 solutions - Sadun, Erica (Sybex, Inc., 2004)
While DVD Studio Pro 2 is a full-featured, affordable DVD authoring program, this book is a full-featured, affordable aide that teaches you how to achieve immediate, impressive results. Learn how to encode audio and video; build menus; add language tracks, subtitles, and captions; web-enable your DVD; write scripts; protect your DVD; create DVD slide shows; and much more. Acclaimed Mac author Erica Sadun demonstrates real-world professional solutions using her easy-to-follow approach, then backs them up with a packed DVD that includes 50 example projects; sample video, audio, and slide shows; third-party product demos; and source code.